Effect of a complex intervention to improve post-vision screening referral compliance among pre-school children in China: A cluster randomized clinical trial. (February 2020) - Zeng, Yangfa; Han, Xiaotong; Wang, Decai; Chen, Shida; Zheng, Yingfeng; Jiang, Yuzhen; Chen, Xiang; Li, Yuting; Jin, Ling; Chen, Qianyun; Liang, Xiaoling; Zhang, Xiulan; et al.
Abstract: Background: We investigated whether specific appointments for quality-assured care could increase referral uptake, often low in China, in children's vision screening. Methods: We randomized children aged 4–7 years in Yudu, Jiangxi, China, by school to Control (free school-based eye screening, parents of children failing screening recommended for further examination [usual practice]) or Intervention (identical examinations, with parents additionally provided with specific appointments for further examinations by quality-assured doctors at a designated local hospital). Both groups could select any hospital for referral exams, which were not free. Six months after screening, parents were interviewed on referral compliance at any hospital (primary outcome) and potential determinants. This trial is registered at the ClinicalTrials.gov, number NCT 03251456. Findings: Among 9936 children at 63 schools randomized to Intervention (32 schools, 5053 [50·9%] children) or Control (31 schools, 4883 [49·1%] children), 1114 children (11·2%) failed screening. Among 513 referred Intervention children (46·1%, 32 schools, mean age 5·36 years, 53·0% boys) and 601 referred Control children (53·9%, 31 schools, mean age 5·30 years, 57·7% boys), 104 (20·3%) and 135 (22·5%) were lost to follow-up respectively. Under Intention to Treat analysis, assuming children lost to follow-up were non-compliant, Intervention children had significantly higher compliance than Controls (308/513 = 60·0% vs. 225/601 = 37·4%, P  < 0·001). In regression models, Intervention group membership (Relative risk [RR] 1·53, 95% confidence interval, 1·36–1·72), travel time to hospital (RR: 0·97, 0·95–0·999), baseline glasses wear (RR: 1·37, 1·17–1·60), strabismus (RR: 1·17, 1·01–1·36) and worse uncorrected vision (RR: 1·41, 1·03–1·92) were associated with compliance. Interpretation: Providing specific appointments for quality-assured eye care improved referral compliance in this setting.